EVALUATION OF THE EFFECTIVENESS OF BIOFEEDBACK TECHNOLOGY FOR LOCOMOTIVE CREW WORKERS - Несина, Ирина Алексеевна; Джафарова, Ольга Андреевна; Потеряева, Елена Леонидовна; Смирнова, Елена Леонидовна; Кулишова, Тамара Викторовна (Medicine in Kuzbass, 2025)
Employees of locomotive crews of mainline traffic constitute a professional group directly ensuring the safety of the transportation process. The professional activity of locomotive crew employees requires constant responsibility, readiness to operate in extreme conditions or non-standard situations, and promptness in decisions and actions. The main causes of violations in the performance of work functions are violations of the psychophysiological state as a result of prolonged exposure to negative factors of the working environment. The aim of the research – to evaluate the effectiveness of biotechnology for locomotive crew workers. Materials and methods. The study involved 346 employees of locomotive crews (machinists and assistant machinists). To conduct biofeedback sessions (BOS training), a «Hardware and software complex with a Pulse module (game console) for treatment and rehabilitation using biofeedback BOS PULSE» method was used. To assess changes in well-being and stress tolerance as a result of the BOS course, testing was conducted before and after it, and the following methods were used: «Self-assessment of mental state: well-being, activity, mood» (SAN), «Coping behavior in stressful situations» (CISS) (adaptation by T.L. Kryukova). The reliability of the changes was assessed using nonparametric methods of mathematical statistics, namely, the Wilcoxon and Kruskal-Wallic tests; the analysis was carried out using the STATISTICA application. Results. The analysis of the self-assessment survey of the results of the BOS training allowed us to identify 3 groups: group 1 – 194 people (56%) – indicated the ability to manage their emotional state as the main result; group 2 – 114 people (33%) – noted the improvement/development of self-regulation skills; group 3 – 38 people (11%) – they did not feel any changes in their emotional state, could not formulate the result of the training, i.e. this group can be described as «unchanged». Conclusion. The biofeedback training should be used in programs of psychocorrection, psychophysiological support of physical therapy, primarily for training self-regulation, management of physiological parameters – normalization of heart rate, relief of muscle tension, as well as for the development of skills for rapid recovery after psychoemotional and physical exertion.